The current status of nano-hydrogel preparations for osteochondral repair: Systematic Review - Abebe Feyissa Amhare; Abebe Feyissa Amhare; Lichun Qiao; Huan Deng; Jinyan Lin; Jun Wang; Wei Wang; Jing Han (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundOsteochondral defects, involving both cartilage and subchondral bone, remain clinically challenging due to the poor intrinsic healing capacity of cartilage and the limited durability of traditional treatments. This systematic review aims to evaluate current advancements in nano-hydrogel formulations for osteochondral repair, focusing on their composition, preparation methods, mechanical properties, biocompatibility, and regenerative outcomes.MethodsFollowing the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, a comprehensive literature search was conducted across PubMed, Web of Science, and Scopus. Eligible studies were screened based on predefined inclusion and exclusion criteria. The methodological quality and risk of bias of included studies were assessed using CAMARADES checklist, which considered factors such as randomization, blinding, animal welfare compliance, outcome reporting, and study reproducibility. Data synthesis was performed through structured tabulation and subgroup stratification by scaffold structure (single-phase, bilayered, trilayered, gradient), formulation type (injectable vs. preformed), and polymer origin (natural, synthetic, hybrid).ResultsA total of 41 studies were included, encompassing both in vitro and in vivo models, with participant numbers ranging from small animal models (e.g., rabbits, rats) to larger preclinical systems. Studies varied in scaffold design, bioactive integration, and fabrication techniques. Most nano-hydrogels demonstrated high biocompatibility, tunable degradation, and enhanced tissue integration. However, heterogeneity in design parameters, lack of standardized outcome measures, and variable reporting quality limited direct comparisons.ConclusionNano-hydrogels show strong potential as biomimetic scaffolds for osteochondral repair, offering customizable mechanical and biological properties. Nevertheless, the evidence base is limited by study heterogeneity, moderate risk of bias, and lack of standardized protocols, which complicates direct comparison and clinical extrapolation. Future work should focus on long-term validation, functional outcome measures, and development of smart, adaptive materials to support clinical translation.